Exploring The Perspectives On The Management And Evaluation Of The Impact Of Clinical Pharmacist Intervention On Drug Therapy Problems In Ambulatory Patients With Chronic Kidney Disease: A Mixed-Method Approach - Alam, Khurshid (2024)
Chronic kidney disease (CKD) is the irreversible loss of normal kidney functions that is a slow and progressive disease. Chronic kidney disease is a widespread global health problem, yet there exists a notable gap in understanding the factors that shape treatment preferences according to the perspectives of patients and caregivers. The study aim was to conduct a novel qualitative study to explore the perspectives and experiences of patients and their carers' nephrologists, regarding the management of patients with CKD and to evaluate the prevalence of drug-related problems (DRPs) and the impact of clinical pharmacists on DRPs in ambulatory patients. A mixed-method study approach (qualitative and quantitative) was employed. A total of 11 nephrology experts and 19 CKD patients were included in the qualitative study. A descriptive phenomenological approach was used, entailing one-on-one semi-structured interviews to explore the perspectives and live experiences of nephrology experts and patients diagnosed with CKD. In the quantitative phase, a single-arm, pre and post-intervention study design was used.